Desigualdade ocupacional no mercado de trabalho formal brasileiro: uma análise da distribuição de salários no século XXI - Amanda Ferrari Uceli (2023)
The purpose of this thesis was to demonstrate the occupational structure importance for Brazilian formal labor market wage inequality, bringing evidence of inequality persistence between occupations, compared to individuals, in the context of economic structural changes from 2003 to 2020. During this time, marked cycles defined the economy and politics in Brazil, standing in the period until 2014, when a virtuous cycle was responsible for the reduction in inequality with the growth of the formal labor market. From 2015 until the present, the economy and politics began a vicious cycle marked by crises that reversed the gains from the former period. In this context, the labor market was a way to propagate economic cycles and was a fundamental indicator of economic performance. The significant change in occupational structure during these years helps to understand the wage distribution changes over time. However, there is a lack of studies that analyze Brazilian wage inequality from inter and intra-occupational perspectives, particularly after 2015. Therefore, this dissertation seeks to answer how inter and intra-occupational inequalities impact the distribution of wages for occupations in the Brazilian formal labor market between 2003 and 2020. Moreover, this dissertation question has this distribution has become less unequal over this period of time? The guiding hypothesis assumes that inequality between occupations is rigid in the analyzed period as a result of intra-occupational, especially from gender gaps, added to growing and persistent inter-occupational inequality over the wage distribution quantiles. The analysis of the ratio indicators of the wage distribution quantiles at the level of individuals and occupations showed that it was possible to verify the rigidity of inter-occupational inequality in contrast to the reduction of inequality at the level of individuals, mainly from 2003 to 2014. In order to test the proposed hypothesis, a panel of occupations was built based on the 3-digit occupational subgroup, on which Powell's Quantile Regression Model with Nonadditive Fixed Effects (QRPD) (2022) was estimated. The results from the model indicated that the stability of inter- occupational wage inequality is related to the composition of the workforce in occupations, with the effect of structural inequalities being greater as one approaches the top of the distribution. Additionally, when measured by the 99/10 ratio, it was noticed that gender inequality decreased during the period of growth of the formal labor market. The results of the QRPD model for gender inequality in the panel of occupations showed how much, at the top of the distribution, intra-occupational inequality neutralizes the conjunctural effect. Among lower-income occupations, these effects add up, reinforcing inter-occupational inequality. The main contribution of this dissertation was to bring evidence of the fundamental role of occupational structure in determining and comprehending Brazilian wage inequality, as so how economic cycles act over labor. In addition, the data and methodological approach give new perspectives to the current wage inequality discussion.